Les représentations du cheval dans l’œuvre d’un artiste à la fin du XIXe siècle : Armand Charnay - Danièle Miguet (In Situ)
The representations of horses in the work of a late-nineteenth-century artist, Armand Charnay. Although he is not considered as a wildlife artist, Armand Charnay (1844-1915) populated his paintings and drawings with many animals, depicting them with accuracy and vividness. Among these animals, horses are often present, and it is interesting to consider the types of horses he shows and the human activities with which they are associated. The artist came from the middle class, the son of a notary, who always lived in a rural environment, first in Charlieu, in the Loire department, then in Marlotte in the forest of Fontainebleau. How did he see the horse? How did he represent it? What horse-related activities do not feature in his work? These are some of the questions that this paper will look at, making comparisons with other modern artists. It will be suggested that the pictures of horses reflect a particular social vision and reveal aspirations that go beyond the mere representation of an animal species.